Clinical Characteristics, Health Care Utilization and Costs Among Men with Primary or Secondary Hypogonadism in a US Commercially Insured Population. Issue 1 (8th December 2016) - Grabner, Michael; Bodhani, Amit; Khandelwal, Nikhil; Palli, Swetha; Bonine, Nicole; Khera, Mohit
Abstract: Introduction: Hypogonadism is broadly associated with increases in chronic comorbid conditions and health care costs. Little is known about the specific impact of primary and secondary hypogonadism on health care costs. Aim: To characterize the health care cost and utilization burden of primary and secondary hypogonadism in a population of US men with commercial insurance. Methods: Newly diagnosed patients with International Classification of Diseases, Ninth Revision, Clinical Modification codes associated with specific medical conditions known to have a high prevalence of testosterone deficiency (ie, relating to primary or secondary hypogonadism) or who had fills for testosterone replacement therapy from January 1, 2007 through April 30, 2013 were identified in administrative claims data from the HealthCore Integrated Research Database. A cohort of patients without hypogonadism was matched on demographics and comorbidities. The matched hypogonadism and non-hypogonadism cohorts (n = 5, 777 in each cohort) were compared during a 12-month follow-up period. Main Outcome Measures: Direct health care expenditures and utilization were assessed for all causes and for hypogonadism-related claims. Costs included out-of-pocket patient expenditures and those paid by the insurer. Results: Hypogonadism and matched non-hypogonadism cohorts were similar in demographics (mean age = 50 years) and diagnosed comorbid conditions in the 12 months preceding the index date. In the year after the index date, mean all-cause expenditures for patients with hypogonadism increased by 62% (from $5, 425 to $8, 813) compared with 25% for the matched controls (from $4, 786 to $5, 992; P < .01 for follow-up difference between groups). Approximately 16% of total mean costs ($1, 377), primarily outpatient and pharmacy costs, were identifiable as related to hypogonadism. Conclusion: These data from a population of US men with commercial insurance coverage showed a greater resource use burden for patients with primary and secondary hypogonadism compared with similar patients without hypogonadism. Additional management might be required to address unmet need and decrease the cost burden for patients with hypogonadism.